2013
DOI: 10.1523/jneurosci.2793-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cathodal Trans-Spinal Direct Current Stimulation on Mouse Spinal Network and Complex Multijoint Movements

Abstract: Cathodal trans-spinal direct current (c-tsDC) stimulation is a powerful technique to modulate spinal excitability. However, the manner in which c-tsDC stimulation modulates cortically evoked simple single-joint and complex multijoint movements is unknown. To address this issue, anesthetized mice were suspended with the hindlimb allowed to move freely in space. Simple and complex multijoint movements were elicited with short and prolonged trains of electrical stimulation, respectively, delivered to the area of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 58 publications
6
52
0
Order By: Relevance
“…This agrees with previous studies, despite differences in location of the return electrode (Fuortes, 1954;Eccles et al, 1962). Recently, we showed that trans-spinal direct current stimulation (DCS) modulates spinal interneuron excitability (Ahmed, 2013b). In addition, trans-spinal DCS had previously been shown to modulate the excitability of primary afferent fibers via their presynaptic terminals (Eccles et al, 1962).…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…This agrees with previous studies, despite differences in location of the return electrode (Fuortes, 1954;Eccles et al, 1962). Recently, we showed that trans-spinal direct current stimulation (DCS) modulates spinal interneuron excitability (Ahmed, 2013b). In addition, trans-spinal DCS had previously been shown to modulate the excitability of primary afferent fibers via their presynaptic terminals (Eccles et al, 1962).…”
Section: Introductionsupporting
confidence: 91%
“…The two lengthening velocities used were within the range that can be produced by cortically evoked dorsiflexion in mice (Ahmed, 2013b 1). In addition, stretch-induced nerve discharges were higher in animals with spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the light of our results and based on our current understanding of tsDCS mechanisms , it is conceivable that the mechanisms underlying enhanced DiMEPs after tsDCS could also involve changes in neurotransmission, which would be in line with the fact that (1) glutamate drives the pathway to PMNs during inspiration (McCrimmon et al, 1989;Chitravanshi and Sapru, 1996) and modulates synaptic strength in the short and long term via NMDA receptors (Rekling et al, 2000;McGuire et al, 2008); (2) GABA is intimately involved in respiratory motor control, as PMNs are inhibited by GABA A receptors during the expiratory phase of respiration (Fedorko et al, 1983;Merrill and Fedorko, 1984); and, (3) PMN NMDA receptors also contribute to excitatory neurotransmission (Chitravanshi and Sapru, 1996) and are implicated in many models of plasticity including phrenic LTF (Golder, 2009). This idea is also supported by recent arguments from animal studies: (1) both anodal and cathodal tsDCS increased glutamate analog D-2,3-3 H-aspartic acid release in vitro (Ahmed and Wieraszko, 2012), and (2) it has been proposed that cathodal tsDCS may act by directly inhibiting the spinal GABAergic system or by exerting overexcitation of postsynaptic neurons (Ahmed, 2013) likely through increased glutamate release (Ahmed and Wieraszko, 2012). The fact that The INTERVENTION factor consists of three levels: anodal, cathodal, and sham tsDCS.…”
Section: Discussionmentioning
confidence: 55%